Peran Tata Kelola Perusahaan dalam Memediasi Hubungan antara CSR dan Nilai Perusahaan pada Sektor Manufaktur: Bukti dari Pasar Negara Berkembang: The Role of Corporate Governance in Mediating the Relationship between CSR and Firm Value in the Manufacturing Sector: Evidence from Emerging Markets - Prasetyo, Budhi Sriyono; Susanti, Daru (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) on firm value with Corporate Governance (CG) as a mediating variable within manufacturing companies in emerging markets. The manufacturing sector was selected due to its significant environmental impact and high regulatory pressure. Using panel data from 2020 to 2024, this study applies path analysis assisted by statistical software. The results indicate that CSR has a direct positive influence on firm value. Furthermore, it was found that strong corporate governance mechanisms significantly mediate this relationship, demonstrating that governance transparency enhances the credibility of CSR reporting in the eyes of investors.